2019
DOI: 10.1139/cjb-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of inbreeding depression and enhanced fitness in cleistogamous progeny in the annual plantTriodanis perfoliata

Abstract: The maintenance of outcrossing in cleistogamous plants that produce both open, facultatively outcrossing chasmogamous (CH), and closed, obligate selfing cleistogamous (CL) flowers is puzzling because CL reproduction is thought to be more reliable and less costly. A possible explanation for the maintenance of CH flowers is the avoidance of inbreeding depression. However, inbreeding depression for cleistogamous species has rarely been quantified. In this study, we estimate levels of inbreeding depression in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Dimorphic cleistogamy is thought to be an advantageous reproductive strategy that allows for plastic responses in sexual reproduction depending on the quality of pollination and abiotic resource environment ( e.g . Ansaldi et al 2019). In this study we found that cleistogamy expression in C. broussonetii is maximized in abiotically degraded frequently burned habitats from Chaco Serrano that apparently did not show depleted pollination fauna.…”
Section: Discussionmentioning
confidence: 98%
“…Dimorphic cleistogamy is thought to be an advantageous reproductive strategy that allows for plastic responses in sexual reproduction depending on the quality of pollination and abiotic resource environment ( e.g . Ansaldi et al 2019). In this study we found that cleistogamy expression in C. broussonetii is maximized in abiotically degraded frequently burned habitats from Chaco Serrano that apparently did not show depleted pollination fauna.…”
Section: Discussionmentioning
confidence: 98%
“…Self‐fertilization is common in flowering plants and frequently gives rise to inbreeding depression, defined as a reduction in the fitness of inbred relative to outbred offspring. Extensive work has documented effects of inbreeding on a wide range of fitness‐related plant traits, including growth and reproductive output through both the male (e.g., pollen production, pollen viability, pollen tube growth) and female (e.g., fruit and seed production) functions (Husband and Schemske, 1996; Jóhannsson et al, 1998; Ansaldi et al, 2019). Recent work has also begun exploring the ecological implications of inbreeding, including interactions among plants and other organisms (Stephenson et al, 2004; Carr and Eubanks, 2014; Kalske et al, 2014; Haber et al, 2018; Schrieber et al, 2018; Kariyat and Stephenson, 2019).…”
mentioning
confidence: 99%
“…A mixed mating system in which both closed, obligate selfing cleistogamous (hereafter CL) flowers and open, facultatively outcrossing chasmogamous (hereafter CH) flowers are produced on the same individual, is a relatively widespread condition occurring in around 50 angiosperm families (Lord, 1981; Culley and Klooster, 2007). Compared to CH flowers, CL flowers are cheaper to produce, more reliable in terms of fruit set, and have higher seedling emergence (Baskin and Baskin, 2017; Ansaldi et al, 2019). Cleistogamy has evolved independently multiple times (Desfeux et al, 1996), and there are few, if any, documented cases of loss of the CH flowers.…”
mentioning
confidence: 99%
“…Cleistogamy has evolved independently multiple times (Desfeux et al, 1996), and there are few, if any, documented cases of loss of the CH flowers. This peculiar reproductive strategy, and why it is maintained, has puzzled biologists for a long time, and continues to do so because it goes against the prediction that mixed mating is not evolutionarily stable (Goodwillie et al, 2005; Oakley and Winn, 2008; Winn and Moriuchi, 2009; Ansaldi et al, 2019; Furukawa et al, 2020). Yet, experimental studies have revealed certain conditions (e.g., pollen limitation) that would allow mixed mating systems to be evolutionarily stable (Albert et al, 2011; Stojanova et al, 2020).…”
mentioning
confidence: 99%